The different member equivalent circulating density prediction model and drilling parameter optimization under narrow density window - Zhao, Wanchun; Yang, Zhipeng; Wang, Tingting; Zhou, Yan; Song, Wei; Li, Jingrun; Zhai, Peihong (Frontiers in Earth Science, 2025)
Wellbore stability is a key factor in ensuring safe and efficient drilling operations. The variation in Equivalent Circulating Density (ECD) has a significant impact on safety, economics, and drilling progress. As unconventional resources like shale gas and tight oil are explored, geological conditions and reservoir characteristics have become more complex. These complexities lead to narrower density windows, making precise ECD control essential. Proper control can prevent incidents such as lost circulation, blowouts, and wellbore collapse. This study establishes a new ECD calculation model. The model accounts for total fluid pressure loss, formation temperature, and formation pressure. An ECD prediction model based on drilling parameters and segmented reservoir layers is also proposed. The model uses nonlinear regression algorithms to predict ECD values for different members. It integrates real-time drilling data such as depth, drilling pressure, displacement, and rotational speed, along with formation temperature and pressure. The model also optimizes drilling parameters to keep the ECD within the safe density window. Case studies from a high-temperature, high-pressure volcaniclastic reservoir well in the Nanpu region validate the models. The correlation coefficients (R2) of the calculation and prediction models exceed 0.99. After optimization, the ECD for Ed2, Ed3, Es1, and Es31 remains within the safe window. This significantly improves wellbore stability and ensures operational safety. The results reveal notable differences in regression coefficients across different members. This confirms the necessity of using member-specific ECD prediction models. Additionally, the safe parameter ranges provided by this study offer practical guidance for drilling design. These models have broad application prospects, especially in complex geological environments.